Harassment and stalking of Members of the United Kingdom Parliament: associations and consequences. Issue 3 (3rd May 2016) - James, David V.; Sukhwal, Seema; Farnham, Frank R.; Evans, Julie; Barrie, Claire; Taylor, Alice; Wilson, Simon P.
Abstract: A survey concerning intrusive/aggressive behaviours towards MPs was administered at Westminster, and in Queensland, New Zealand and Norway. Follow-up interviews were conducted with a sample at Westminster. This paper examines the experiences and associations of the 239 Westminster responders, of whom 81% had experienced intrusive/aggressive behaviours, 18% been subject to attack/attempted attack, and 53% stalked or harassed. Being stalked and subject to certain types of intrusive/aggressive behaviour were associated with younger age and being in the Commons five years or less, but serious incidents were more common in those who had been MPs for longer. There were no associations with brief periods of harassment. Some differences with party and constituency type emerged. Mental illness was prominent amongst perpetrators. Motives predominantly concerned personal grievances. Significant proportions of MPs suffered psychological ill-effects, necessitating inconvenient behaviour changes. Internal consistencies in these results and similarities to other sites are explored, and their implications discussed.